Current pest status of cassava and their management strategies in Cameroon - Tindo, M.; Njukwe, E.; Mbairanodji, A.; Tenkouano, A. (2017)
We conducted two main surveys during dry seasons of 2008 and 2009 in 29 sites within the five pilot zones of the “Programme National de Développement des Racines et Tubercules” (PNDRT)-Cameroon to assess potential changes triggered by the introduction of improved varieties on cassava pest status. Standard methods were used to evaluate pest incidences, populations and damages, natural enemies’ occurrences, on both local and improved varieties. Seven pre-dominant pest species were found including the cassava mealybug, cassava green mite (CGM), cassava red mite, to-bacco white-fly, spiralling white-fly, the African root and tuber scale and the variegated grasshopper. Incidence, number of individuals and damages severity of all pests varied considerably between survey dates, pilot zones and varieties but were controversial. More pests were observed and their incidence and severity were higher during the first than the second surveys. Local varieties were significantly more attacked during the first survey but the contrary was observed during the second survey in 2009. Natural enemies of CGM were observed but not in all the pilot zones. One can con-clude that the introduction of improved cassava varieties is not significantly affecting the cassava pest status. Collabora-tive efforts should, therefore, continue to develop, select and introduce resistant materials against major pests.